2018
DOI: 10.1007/s13555-018-0243-4
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Scoping Literature Review of Publications Supporting Treatment Guidelines for Pediatric Atopic Dermatitis in Contrast to Clinical Practice Patterns

Abstract: IntroductionTreatment guidelines endorse a variety of strategies for atopic dermatitis (AD) which may vary from published data and clinical practice patterns. The objective of this review was to quantify the volume of available medical literature supporting pediatric AD treatments and compare these patterns to those recommended by published guidelines and/or clinical practice patterns.MethodsSearches of Embase (2005–2016) and abstracts from selected meetings (2014–2016) related to AD treatment in patients youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 211 publications
1
5
0
Order By: Relevance
“…As for TCSs, dermatologists might have more comfort with the risk-benefit profile of this class of treatments when used as prescribed. 10 There was widespread use of medications not recommended by published AD guidelines, consistent with a previously published observational study. 21 Oral antihistamines were the most commonly used agents after TCSs, despite concerns over adverse effects, such as undesired sedation, dry mouth, and blurred vision, which might be particularly detrimental for school-aged children.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As for TCSs, dermatologists might have more comfort with the risk-benefit profile of this class of treatments when used as prescribed. 10 There was widespread use of medications not recommended by published AD guidelines, consistent with a previously published observational study. 21 Oral antihistamines were the most commonly used agents after TCSs, despite concerns over adverse effects, such as undesired sedation, dry mouth, and blurred vision, which might be particularly detrimental for school-aged children.…”
Section: Discussionsupporting
confidence: 79%
“…Published literature is scant on current pediatricspecific practice patterns. 10 The objective of this study was to assess current treatment patterns in a large population of insured pediatric patients with AD to identify opportunities for improved management.…”
mentioning
confidence: 99%
“…There are notable discrepancies in the literature regarding paediatric patients treated with TCIs. In a review by Siegfried et al., TCI treatment ranged from 0% to 52% [ 6 ]. Accordingly, we found that only 5% of the patients received TCIs, consistent with Paller et al.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of the clinical picture and disease course of patients with AD indicates a complex reality and uncertain disease trajectories. The literature on treatment patterns and disease severity, particularly in patients under 2 years of age, is sparse [5,6]. A review by Siegfried et al [6] revealed limited data on longterm and combination treatment, treatment of severe AD, and systemic corticosteroids in children [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation